PERAN DUKUNGAN SOSIAL BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DALAM PENANGANAN KORBAN BENCANA DI KOTA SURAKARTA - Yuliana; Dhian Riskiana Putri; Anniez Rachmawati Musslifah (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2026)
THE ROLE OF SOCIAL SUPPORT FROM THE REGIONAL DISASTER MANAGEMENT AGENCY (BPBD) IN HANDLING DISASTER VICTIMS IN SURAKARTA CITY Natural disasters are events that can cause damage and loss of life. Natural disasters are unavoidable events that often leave deep scars of suffering for the individuals and communities affected. Disaster management in Surakarta City is regulated in an integrated manner by the Regional Disaster Management Agency (BPBD) of Surakarta City, which focuses on mitigation, preparedness, emergency response, and recovery. In handling disaster victims, social support is a very important factor. This study aims to determine the role of social support provided by BPBD officers in handling disaster victims in Surakarta City. This study uses a qualitative approach with data collection techniques in the form of interviews and participatory observation, which were conducted directly through the involvement of seven BPBD officers as informants. The data analysis techniques used include data reduction, data presentation, and conclusion drawing. The results of the study indicate that BPBD officers provide good social support in handling disaster victims in Surakarta City. The social support provided includes emotional support, informational support, and instrumental support. This study also shows that social support plays an important and positive role for BPBD officers in carrying out their duties. Social support not only plays a role in the process of handling victims, but also functions as an effective stress reliever for officers in dealing with disaster situations.